EXPRESSIVE SPEECH ACTS ON SAM SMITH'S INSTAGRAM ACCOUNT COMMENTS - Albert Ryan Ramaputra; Priska Meilasari (Humaniora Scientia, 2023)
The purpose of this study is to explain the types and functions contained in comments on Sam Smith's Instagram account. The research design is descriptive qualitative. The data in this study are utterances that contain expressive speech acts. The data collection technique was carried out by collecting data from Instagram comments on Sam Smith's Instagram account in a post stating that her new album entitled Gloria has been released. Data in the form of comments were classified and analyzed according to the types and functions of expressive speech acts based on Norrick’s (1987) classification.Differences in each comment contained in Gloria's post is that each character in the comment has its expressive type - including those using expressive speech acts of thanking, expressive speech acts of greeting, expressive praise speech acts, and expressive complimentary speech acts. The fifty-two data contained in this study included five types of expressive speech acts taken from nine types based on Norrick’s classification. The five types found in the comments includes expressive speech acts of thanking (11 data), expressive speech acts of praising (28 data), expressive speech acts of greeting (10 data), expressive speech acts of protesting (1 datum), and expressive speech acts of complaining (1 datum). Furthermore, the functions of expressive speech acts are classified based on each type. The expressive speech act of thanking functions to convey the speaker's gratitude to the listener, and to convey the speaker's appreciation for the benefits that have been given by the interlocutor. The functions of expressive speech act of praising includes expressing the speaker's admiration to the album, expressing the speaker's approval of something, expressing the speaker's admiration for the song, and expressing the speaker's admiration for the photo. The expressive speech act of Greeting is used to welcome someone's arrival. The function of the expressive speech act of complaining is to show disappointment with something whereas the function of the expressive speech act of protesting is to criticize undesired actions performed by listeners.The result of the study could contribute to the deeper analysis of expressive speech acts in the field of pragmatics. Perhaps the implication of the result of the study would give more understanding of expressive speech acts used in social media. Keywords: Pragmatics: speech acts, types of speech acts, function of speech acts.